Crystal structure landscape of ethenzamide: a physicochemical property study. Issue 5 (13th January 2017) - Sarmah, Kashyap Kumar; Boro, Kaveri; Arhangelskis, Mihails; Thakuria, Ranjit
Abstract : Pharmaceutical cocrystals/cocrystal hydrate of ethenzamide (ETZ) with various hydroxy-acid coformers namely 24DHBA, 35DHBA, FRA, and 35DHBA dihydrate (1 : 3 : 2) were synthesised and characterised thoroughly. The solubility order of ETZ cocrystals was explained based on the coformer's solubility, hydrogen bond interactions and crystal morphology. Abstract : Pharmaceutical cocrystals/cocrystal hydrate of ethenzamide (ETZ) with various hydroxy-acid coformers namely 2, 4-dihydroxybenzoic acid (24DHBA), 3, 5-dihydroxybenzoic acid (35DHBA), ferulic acid (FRA, nutraceutical molecule) and 35DHBA dihydrate (1 : 3 : 2) were synthesised using solution crystallisation as well as mechanical grinding. All the multi-component systems were characterised using various solid-state characterisation techniques such as single crystal X-ray diffraction (SCXRD), powder X-ray diffraction (PXRD), differential scanning calorimetry (DSC) and FT-IR spectroscopy. Structural analysis reveals that the position of the hydroxyl group governs the hydrogen bond synthon present in the cocrystals/cocrystal hydrate system. ETZ·24DHBA has an unusual amide–amide catemer synthon and is 3D isostructural to the reported ETZ·4HBA cocrystal. The solubility study shows that the ETZ·35DHBA cocrystal is 13 times more soluble in water compared to pure ETZ. The solubility order of ETZ cocrystals along with pure ETZ can be represented as ETZ·35DHBA > ETZ·24DHBA > ETZ > ETZ·FRA, and follows the trend of the coformer's solubility.